The Influence of Customer Reviews, Influencer Reviews, Celebrity Endorsers, and Trust on Purchase Intention - Helmi siti Faojiah; Andri Kusmayadi (The Future of Education Journal, 2026)
Purchase intention plays an important role in marketing strategies that can be implemented by Wardah by providing the best facilities and services for consumers in order to build trust and satisfaction, thereby encouraging continuous product purchases. This study aims to identify the most influential factors affecting purchase intention. This research employed a quantitative approach using a purposive sampling technique. Data were collected through questionnaires distributed to 110 Generation Z respondents who actively use social media, follow Wardah’s official social media accounts, are between 17 and 26 years old, and reside in Jakarta. Primary data were analyzed using the Structural Equation Modeling (SEM) method. The results indicate that five out of the seven proposed hypotheses were accepted, and the trust variable had the strongest direct influence on purchase intention. This study contributes to Wardah’s efforts to maintain and enhance purchase intention by considering several factors derived from consumer complaints in an optimal and measurable manner. For future research, it is recommended to expand the research area and investigate objects in other fields.